2011
DOI: 10.1038/ejcn.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Beverage-specific alcohol intake and bone loss in older men and women: a longitudinal study

Abstract: Background/Objectives: There is inconsistent evidence regarding the association between moderate alcohol consumption and bone mineral density (BMD). The aim of this study was to describe the associations between total and beverage-specific alcohol intake and bone loss in older men and women. Subject/Methods: A total of 862 randomly selected subjects (mean age 63 years, range 51-81, 51% men) were studied at baseline and 2 years later. BMD was assessed by dual-energy X-ray absorptiometry. Beverage specific and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…It is still much discussed whether the consumption of alcohol is a risk factor or protection factor for BMD. Studies indicate that, besides the amount of alcohol ingested, the quality of the alcohol can affect this association [ 27 ]. This could be related to the beneficial influence of nonalcoholic compositions on the health of bones [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is still much discussed whether the consumption of alcohol is a risk factor or protection factor for BMD. Studies indicate that, besides the amount of alcohol ingested, the quality of the alcohol can affect this association [ 27 ]. This could be related to the beneficial influence of nonalcoholic compositions on the health of bones [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have shown that high dietary caffeine intake is associated with reduced BMD and increased urinary calcium loss [ 8 , 13 ]. In addition, both alcohol and caffeine have been implicated in the development of osteoporosis in patients at risk [ 11 , 13 , 14 ]. These factors are associated with an increased risk of hip fracture [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The work by Yin et al. [36] also showed that ingestion of red wine prevented bone resorption in older men, while the same was true with beer drinking among women. However, the association was weak [35] .…”
Section: Discussionmentioning
confidence: 87%